2019
DOI: 10.4274/tpd.galenos.2019.6218
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Cystic Echinococcosis Results in Aydın Adnan Menderes University Training and Research Hospital Parasitology Laboratory Between 2005 and 2017

Abstract: Objective: Echinococcus granulosus is the causative helminth of cystic echinococcosis (CE). The parasite is known to form fluidfilled cysts that grow slowly in the internal organs, particularly the liver and/or lungs. This disease is still important in terms of public health and economically in Turkey and other countries where animal husbandry is widespread. The aim of our study was to retrospectively evaluate the cases that were admitted to the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…In a Chinese study between 2004 and 2013, 60.7% of the reported histopathologically-confirmed CE cases 19 . The seroprevalence of CE in the present study was similar 11, [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In a Chinese study between 2004 and 2013, 60.7% of the reported histopathologically-confirmed CE cases 19 . The seroprevalence of CE in the present study was similar 11, [16][17][18][19] .…”
Section: Discussionsupporting
confidence: 77%
“…Güreser et al reported that 23(15.5%) female and 9(8.6%) male patients were seropositive 17 . Ertabaklar et al reported that 642(18.6%) females and 462(13.4%) males were seropositive 18 . In a Chinese study between 2004 and 2013, 60.7% of the reported histopathologically-confirmed CE cases 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An incidence of 0.87 to 6.6 per 100,000 inhabitants has been reported for CE in Turkey [14]. A retrospective analysis of CE in Aydın Adnan Menderes University training and research hospital in Turkey, from 2005 to 2017, reported 247 pathologically confirmed cases [15]. In Pakistan, data regarding human CE is limited [16].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Ertabaklar et al, it was reported that 81.8% of CE were in the liver, 6.1% in the lung and liver, 6.1% in the lung only, and lower rates in other organs (e.g. spleen, kidney, psoas) [32]. In our study, 79 of the 8 patients (76.92%) had multiple localizations; seven were in liver and lung, one was in the liver and intraabdominal cavity.…”
Section: Discussionmentioning
confidence: 65%